GPs' preferences: What price fee-for-service? - Peter Zweifel; Maurus Rischatsch; Angelika Brändle (University of Zurich, Socioeconomic Institute, 2009)
In mixed health care systems a crucial condition for the success of Managed Care (MC) plans is to win over a su±cient number of general practitioners (GPs) acting as gatekeepers. This contribution reports on GPs' willingness-to-accept (WTA) or compensation asked, respectively, for changing from conventional fee-for-service to MC practice. Some 175 Swiss GPs participated in discrete choice experiments which permit to put a money value on their status quo bias. Regardless of whether effects coding or dummy coding is used to measure status quo bias, Swiss GPs require at least 16 percent of their current average income to give up fee-for-service in favor of MC practice.
Keywords: C93; D61; I11; J22; 330; general practitioners; willingness-to-pay; preferences; market experiments; managed care; effects coding; status quo bias; Integrierte Versorgung; Willingness to pay; Basisgesundheitsversorgung; Diskrete Entscheidung; Schweiz